Defence related SME's : analysis and description of current conditions - Carvalho, Fernando Duarte (NATO science series. Science and technology policy ;, 2004)
Today, there are big changes and differences between countries in matters of national defence. Gone are the huge engines of military industrial might, and struggling in their wake are networks upon networks of small and medium-sized enterprises (SME's), groping with the harsh reality of survival in this new world. For the first time, many if not most of them, are being forced to deal with new issues such as product development, marketing to a civilian world, private-sector financing and adopting competitive business practices and generally living outside the shadow of the defence business. Cru.